Cryogenic ferroelectricity of HZO with an aluminum oxide interlayer - Mamidala, Karthik Ram ; 0000-0001-9512-1064; Wernersson, Lars-Erik (IEEE Transactions on Electron Devices, 2025)
In this work, we investigate the cryogenic performance of hafnia-based ferroelectric capacitors with and without an aluminum oxide (ALO) interlayer, comparing conventional metal-ferroelectric-metal (MFM) structures to metal-ferroelectric-insulator-metal (MFIM) counterparts. Devices employing Hf0.5Zr0.5O2 as the ferroelectric layer were characterized from 300 K down to 10 K, targeting temperature ranges relevant to cryogenic logic and quantum memory. Our results reveal that the ultrathin ALO interlayer effectively suppresses leakage across all temperatures while altering the coercive field symmetry and reducing remnant polarization as the temperature is reduced. Dynamic switching measurements and analysis show that MFM capacitors achieve near temperature-independent polarization switching at a 3.0 V WRITE amplitude. In contrast, MFIM devices show more pronounced temperature dependence in the switching behavior, particularly at temperatures below 77 K. While both the MFM and MFIM devices exhibit endurance 107 cycles at 77 and 10 K, the MFIM devices are more affected by polarization fatigue. Benchmarking against state-of-the-art literature values confirms that our MFM and MFIM structures demonstrate among the highest reported 2Pr values below 77 K at low operating voltages ( ≤ 3.5 V). These results highlight the promise of interlayer-engineered hafnia capacitors for low-power cryogenic memory applications.
Keywords: Cryogenic electronics; Ferroelectric; Ferroelectricity; Ferroelectric materials; quantum memory